Transcervical endoscopic retropharyngeal lymph node (RPLN) dissection in nasopharyngeal carcinoma with RPLN recurrence. Issue 1 (28th September 2020) - Liu, You‐Ping; Wang, Shun‐Lan; Zou, Xiong; You, Rui; Yang, Qi; Zhang, Meng‐Xia; Wang, Zhi‐Qiang; Lin, Mei; Xie, Yu‐Long; Chen, Si‐Yuan; Ouyang, Yan‐Feng; Yu, Zi‐Kun; et al.
Abstract: Background: Surgical access for retropharyngeal lymph node (RPLN) dissection is difficult. We aimed to examine the efficacy of transcervical endoscopic RPLN dissection (TSE‐RPLND) for recurrent RPLN in nasopharyngeal carcinoma (NPC). Methods: From April 2013 to February 2019, a total of 31 patients with NPC diagnosed with RPLN recurrence underwent TSE‐RPLND. The clinical characteristics, complications, and survival outcomes were retrospectively analyzed. Results: The mean duration of surgery, quantity of bleeding and postoperative hospitalization stay were 347.9 minutes, 107.7 mL, and 8.7 days, respectively. After a median follow‐up of 31.0 months, the 2‐year locoregional relapse‐free survival, distant metastasis‐free survival, progression‐free survival, and overall survival rates were 63.9%, 95.2%, 59.9%, and 83.3%, respectively. The long‐term incidences of swallowing problems, permanent nutrient tube, tongue atrophy, and shoulder problems were 6 (19.4%), 3 (9.7%), 3 (9.7%), and 3 (9.7%), respectively. Conclusions: TSE‐RPLND is an effective method to treat RPLN recurrence in NPC, but nerve injury‐related complications should not be ignored.